Case report: A de novo ERBB3 mutation develops in a gallbladder cancer patient carrying BRCA1 mutation after effective treatment with olaparib - Yang, Jing-Xiao; Jia, Zi-Yao; Liu, Fa-Tao; Wu, Wen-Guang; Li, Xue-Chuan; Zou, Lu; Li, Huai-Feng; Zhang, Fei; Bao, Run-Fa; Peng, Shu-You; Lau, Wan Yee; Liu, Yun; et al. (Frontiers in Oncology, 2023)
Olaparib, a kind of Poly ADP-ribose polymerase inhibitor (PARPi) has commonly been engaged to treat cancer patients to target BRCA1 with this mutation. A patient with an unresectable gallbladder cancer (GBC) who expressed a germline BRCA1 p.Arg1325Lys heterozygous mutation by next-generation sequencing responded well to an 8 week treatment with olaparib as shown on CT and PET/CT. Dramatically decrease in tumor size allowed the tumor to become resectable. Histological examination showed a shrunken tumor with adequate resection margins, and lymph nodes were negative for metastasis. A follow-up 6 month-olaparib treatment showed the blood level of CA19-9 to decline from 328 U/mL to within the normal range, and no recurrence was detected on CT scanning, indicating a disease-free survival of 6 months. Subsequent CT examination and CA19-9 levels than showed cancer relapse. Liquid biopsy revealed a new ERBB3 p.Gly337Arg mutation to be the cause of drug resistance and relapse. GBC cell lines ectopically expressing dual BRCA1 p.Arg1325Lys and ERBB3 p.Gly337Arg mutations were tested using olaparib and/or ERBB2/3 inhibitor afatinib to investigate the efficacy of targeting BRCA1 and ERBB3 mutation in cultured cells. The combined therapy resulted in notably better suppressed cell survival when compared with a single drug treatment. This is the first case report on a patient with GBC who carried a BRCA1 mutation after effective treatment using olaparib who then developed a ERBB3 muation, suggesting a novel therapeutic strategy which can been used to target BRAC1/2 and ERBB2/3 mutations in GBC.